Stroke recurrence is associated with unfavorable intracranial venous outflow in patients with symptomatic intracranial atherosclerotic large vessel severe stenosis or occlusion - Gao, Jiali; Zhang, Liang; Lin, Jiaxin; Yang, Jiajie; Yao, Mingzheng; Cheng, Zhongyuan; Cai, Xiangran; Huang, Li’an (Frontiers in Neurology, 2023)
Objective The purpose of this study was to investigate the predictive value of intracranial venous outflow for recurrent cerebral ischemic events (RCIE) in patients with symptomatic intracranial atherosclerotic large-vessel severe stenosis or occlusion (sICAS-S/O). Methods This retrospective study included sICAS-S/O patients with anterior circulation who underwent dynamic computed tomography angiography (dCTA) and computed tomography perfusion (CTP). Arterial collaterals were evaluated using the pial arterial filling score for dCTA data, tissue-level collaterals (TLC) were assessed using the high-perfusion intensity ratio (HIR, Tmax >10 s/Tmax >6 s), and cortical veins were evaluated using the multi-phase venous score (MVS) for the vein of Labbé (VOL), sphenoparietal sinus (SPS), and superficial cerebral middle vein (SCMV). The relationships between multi-phase venous outflow (mVO), TLC, and 1-year RCIE were analyzed. Results Ninety-nine patients were included, 37 of whom had unfavorable mVO (mVO−) and 62 of whom had favorable mVO (mVO+). Compared with the mVO+ patients, mVO- patients had a higher admission National Institutes of Health Stroke Scale (NIHSS) score (median, 4 [interquartile range (IQR), 0–9] vs. 1 [IQR, 0–4]; p = 0.048), larger ischemic volume (median, 74.3 [IQR, 10.1–177.9] vs. 20.9 [IQR, 5–86.4] mL; p = 0.042), and worse tissue perfusion (median, 0.04 [IQR, 0–0.17] vs. 0 [IQR, 0–0.03]; p = 0.007). Multivariate regression analysis showed that mVO− was an independent predictor of 1-year RCIE. Conclusion For patients with sICAS-S/O of the anterior circulation, unfavorable intracranial venous outflow is a potential imaging indicator for predicting higher 1-year RCIE risk.